2005
DOI: 10.1128/iai.73.6.3313-3321.2005
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin-Regulated Expression ofBorrelia burgdorferiOuter Surface Protein A In Vivo

Abstract: Borrelia burgdorferi, the agent of Lyme disease, down-regulates outer surface protein A (OspA), which is abundantly expressed in ticks, during infection of the mammalian host. In this study we examined the signals that may be responsible for maintaining the OspA-negative state of spirochetes during infection. Transcription of ospA mRNA was found in tissues of C3H-severe combined immunodeficient (C3H-scid) mice, but not immunocompetent C3H mice, inoculated with cultured B. burgdorferi, tick-borne spirochetes, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
10
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 52 publications
(63 reference statements)
2
10
1
Order By: Relevance
“…To accomplish this, we processed three types of mouse tissue for immunohistochemical labeling of spirochetes during disease remission. We first examined archival tissue from a previous study (30) in which infected C3H-scid mice were immunologically reconstituted at 2 weeks of infection by intravenous adoptive transfer of 2 ϫ 10 7 splenocytes and 1 ϫ 10 7 lymph node cells from naïve C3H mice. At 4 and 6 weeks after adoptive transfer (6 and 8 weeks after infection), mice were necropsied.…”
Section: Induction Of Disease Remission and Tissue Spirochete Reductimentioning
confidence: 99%
See 1 more Smart Citation
“…To accomplish this, we processed three types of mouse tissue for immunohistochemical labeling of spirochetes during disease remission. We first examined archival tissue from a previous study (30) in which infected C3H-scid mice were immunologically reconstituted at 2 weeks of infection by intravenous adoptive transfer of 2 ϫ 10 7 splenocytes and 1 ϫ 10 7 lymph node cells from naïve C3H mice. At 4 and 6 weeks after adoptive transfer (6 and 8 weeks after infection), mice were necropsied.…”
Section: Induction Of Disease Remission and Tissue Spirochete Reductimentioning
confidence: 99%
“…The effect of treatment on spirochete numbers and gene expression in tissues was assessed in heart base, heart ventricular muscle, left tibiotarsus, and quadriceps muscle. These tissues were selected because heart base and tibiotarsus are sites with inflammation, whereas heart ventricular muscle and quadriceps muscle are tissues that are infected, but with minimal inflammation or no inflammation in C3H-scid mice (9,30). Tissue processing for DNA/RNA extraction precluded examination of heart base for carditis.…”
Section: Induction Of Disease Remission and Tissue Spirochete Reductimentioning
confidence: 99%
“…When infected ticks feed again, the spirochetes multiply within the vector, downregulate the production of OspA and infect the host via the salivary glands of the tick. Nonspecific natural antibody in a host may be one signal that down regulates ospA expression (16). Mutants missing OspA and B are able to infect mice and cause disease (28).…”
mentioning
confidence: 99%
“…One signal for downregulation of ospA in the tick is a natural antibody that is acquired during the blood meal (Belperron and Bockenstedt 2001). In contrast, ospA is transcribed in immunodeficient C3H-scid mice, and it has been found that passive transfer of normal mouse serum in infected C3H-scid mice results in ospA downregulation (Hodzic et al 2005). OspA also tends to be expressed in the context of inflammation (Crowley and Huber 2003).…”
Section: Discussionmentioning
confidence: 99%